2017
DOI: 10.1111/jcpp.12695
|View full text |Cite
|
Sign up to set email alerts
|

Income within context: relative income matters for adolescent social satisfaction and mental health

Abstract: Findings are discussed in regard to adolescent socioemotional functioning, as well as the implications for gender differences related to relative income status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
3
9
1
2
Order By: Relevance
“…In addition, our analyses revealed the combined mediating effects of student–teacher relationship and student–student relationship on the association of subjective SES and PYD. The findings extend the previous research showing that adolescents with higher subjective SES are more likely to engage in normative social activities and build positive relationships with teachers and peers compared with their counterparts (Sorhagen & Wurster, ), and these relationships are crucial to promote adolescent PYD via providing effective academic guidance, emotional care, companionship, and overall encouragement to do well in school (Garcia‐Reid, ; Umberson & Karas Montez, ). In addition, the present study documented the specific pathway of subjective SES → student–teacher relationship → student–student relationship → PYD, suggesting that adolescents with higher subjective SES tend to enjoy more positive relationships with teachers, which promote acceptance and connections from peers, which in turn foster positive development.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, our analyses revealed the combined mediating effects of student–teacher relationship and student–student relationship on the association of subjective SES and PYD. The findings extend the previous research showing that adolescents with higher subjective SES are more likely to engage in normative social activities and build positive relationships with teachers and peers compared with their counterparts (Sorhagen & Wurster, ), and these relationships are crucial to promote adolescent PYD via providing effective academic guidance, emotional care, companionship, and overall encouragement to do well in school (Garcia‐Reid, ; Umberson & Karas Montez, ). In addition, the present study documented the specific pathway of subjective SES → student–teacher relationship → student–student relationship → PYD, suggesting that adolescents with higher subjective SES tend to enjoy more positive relationships with teachers, which promote acceptance and connections from peers, which in turn foster positive development.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, our analyses revealed the combined mediating effects of student-teacher relationship and student-student relationship on the association of subjective SES and PYD. The findings extend the previous research showing that adolescents with higher subjective SES are more likely to engage in normative social activities and build positive relationships with teachers and peers compared with their counterparts (Sorhagen & Wurster, 2017), and these relationships are crucial to promote adolescent PYD via providing effective academic guidance, emotional care, companionship, and overall encouragement to do well in school (Garcia-Reid, 2007;Umberson & Karas Montez, 2010).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, Dearing, McCartney, and Taylor (2006) found that income was related to externalizing, but unrelated to internalizing. Moreover, Sorhagen and Wurster (2017) found that relative income (i.e., family income compared to neighborhood income) predicted internalizing and externalizing over and above family socioeconomic status. Though there is much research connecting income to internalizing and externalizing, the precise strength of the relation is hard to estimate.…”
Section: Unpacking the Components Of Socioeconomic Statusmentioning
confidence: 99%
“…These adverse effects, attributable to income inequality in neighbourhoods, have been identified recently in boys 11 and boys and girls. 12 Theories of compound disadvantage 9 predict that the absence of social networks and institutional resources associated with poor neighbourhoods 13 will magnify the disadvantages for children living in poor households. This prediction is supported historically by studies in Europe and North America and is responsible for policies and programs aimed at increasing neighbourhood socioeconomic heterogeneity or "social mix."…”
Section: Neighbourhood Povertymentioning
confidence: 99%